The Impact of Institutioanl Ownership, Inflation, Interest Rates, and ROA on IDX Registered Banking Companies Values During 2017-2019 - Mesrawati, Mesrawati; Kosasih, Draken; Angelica, Angelica; Indrayang, Cecilia; Natasya, Helen (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
This research aims to know the impact of institutional ownership, inflation, interest rate, and Return on Assets (ROA) toward Price Book Value (PBV) of banking companies which are registered in IDX in 2017-2019. This research uses the approach of deductive, quantitative, and descriptive. The population used during the process are of three (3) years. Saturated sample determination that the data aggregates 111 data where three years times thirty seven banking companies which are registered in IDX. The method of data analysis uses the method of multiple linear regression analysis, classic assumption testing and hypothesis testing. The research result is to partially explain that the institutional ownership, inflation, and interest rates do not affect PBV while ROA affects significantly to PBV. Simultaneously, institutional ownership, inflation, interest rates, and ROA effect substantially to the PBV of IDX registered banking companies during 2017-2019. Based on the output of coefficient of determination testing, the value of R Square is 0.115 which means 11,5% variety of PBV variable is described from the variable of institutional ownership, inflation, interest rate, and ROA, the remaining is affected by the other variable in the amount of 88,5%.